2019
DOI: 10.1101/593343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between faecal microbiota and plasma metabolome in rats fed NK603 and MON810 GM maize from the GMO90+ study

Abstract: Safety concerns arising from the consumption of foods derived from genetically modified (GM) crops remains a highly debated and controversial subject. We report here a faecal microbiota compositional analysis in Wistar rats from the GMO90+ study, which fed glyphosate-tolerant NK603 (+/-Roundup application during cultivation) and Bt toxin MON810 GM maize for 6 months (at 11 and 33% composition of the feed) in comparison to their closest non-GM isogenic lines. We first integrated the faecal microbiota compositio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 64 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…In this context the studies reported diverse findings, with an increase of bacteria from Bacteroidetes, 18,[48][49][50][51] Proteobacteria, 16,48,52 Tenericutes, 18,49 Actinobacteria, 49,53 Desulfobacteria, 16 Spirochaetes, 49 Fusobacteria, 12 Deferribacteres 51 and Firmicutes phyla. 49,54 In contrast, some results highlighted a decrease of bacterial numbers from Bacteroidetes, Proteobacteria 12,51,55 and Firmicutes phyla. 18,51,53,55 In addition, it was described that the phyla Gemmatimonadetes, Acidobacteria, Cyanobacteria, Chlorobi, and Nitrospirae were generally altered in the gut after GLY exposure, but the study did not report whether there was an increase or decrease in microorganisms.…”
Section: Effect Of Gly and Its Formulations On The Intestinal Microbiotamentioning
confidence: 93%
See 4 more Smart Citations
“…In this context the studies reported diverse findings, with an increase of bacteria from Bacteroidetes, 18,[48][49][50][51] Proteobacteria, 16,48,52 Tenericutes, 18,49 Actinobacteria, 49,53 Desulfobacteria, 16 Spirochaetes, 49 Fusobacteria, 12 Deferribacteres 51 and Firmicutes phyla. 49,54 In contrast, some results highlighted a decrease of bacterial numbers from Bacteroidetes, Proteobacteria 12,51,55 and Firmicutes phyla. 18,51,53,55 In addition, it was described that the phyla Gemmatimonadetes, Acidobacteria, Cyanobacteria, Chlorobi, and Nitrospirae were generally altered in the gut after GLY exposure, but the study did not report whether there was an increase or decrease in microorganisms.…”
Section: Effect Of Gly and Its Formulations On The Intestinal Microbiotamentioning
confidence: 93%
“…12 Furthermore, it is worth noting that in some studies, differences in gut microbiota composition were identified in each age group and between sexes after herbicide ingestion. Two papers reported a greater impact of GLY and GBH exposure in young animals; 51,53 two papers reported a greater impact in female animals 53,54 and one paper reported a greater impact in male animals. 56 Taking into account the bacterial species, Snodgrassella alvi stands out as one of the most affected species, 44,57,58 in addition to an increase in environmental bacteria in the bee gut, such as Lactobacillus kunkeei and Fructobacillus spp.…”
Section: Effect Of Gly and Its Formulations On The Intestinal Microbiotamentioning
confidence: 98%
See 3 more Smart Citations